2007
DOI: 10.1074/jbc.m702662200
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine Biosynthesis in Arabidopsis thaliana

Abstract: There is much uncertainty as to whether plants use arogenate, phenylpyruvate, or both as obligatory intermediates in Phe biosynthesis, an essential dietary amino acid for humans. This is because both prephenate and arogenate have been reported to undergo decarboxylative dehydration in plants via the action of either arogenate (ADT) or prephenate (PDT) dehydratases; however, neither enzyme(s) nor encoding gene(s) have been isolated and/or functionally characterized. An in silico data mining approach was thus un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
56
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 50 publications
2
56
0
Order By: Relevance
“…The N-terminal domain is unique to plant ADTs and is not found in the bacterial or fungal proteins. In A. thaliana ADTs, this domain is ~100–130 amino acids in length, and are likely to be chloroplast TPs according to sequence prediction programs, which is consistent with phenylalanine biosynthesis occurring in chloroplasts (Jung et al , 1986; Cho et al , 2007; Li and Chiu, 2010) and a chloroplastic localization identified for ADTs in protoplasts (Rippert et al , 2009). …”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…The N-terminal domain is unique to plant ADTs and is not found in the bacterial or fungal proteins. In A. thaliana ADTs, this domain is ~100–130 amino acids in length, and are likely to be chloroplast TPs according to sequence prediction programs, which is consistent with phenylalanine biosynthesis occurring in chloroplasts (Jung et al , 1986; Cho et al , 2007; Li and Chiu, 2010) and a chloroplastic localization identified for ADTs in protoplasts (Rippert et al , 2009). …”
Section: Introductionsupporting
confidence: 68%
“…(A) Phenylalanine can be synthesized in plants using either the prephenate (top) or the arogenate (bottom) pathway (Cho et al , 2007; Maeda and Dudareva, 2012). Prephenate is either decarboxylated/dehydrated to phenylpyruvate (PP) by a prephenate dehydratase (PDT) and PP is then transaminated by a phenylpyruvate aminotransferase (PPAT) to phenylalanine.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations